PRODUCING OF ERYTHRITOL ESTERS WITH STEARIC, PALMITIC AND OLEIC ACIDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
By esterification reaction of 1,2,3,4-tetrachlorobutane with salts of stearic, palmitic and oleic acids corresponding erythritol esters are obtained. The effective methodology for esterification reaction at temperatures 100–190oС with or without solvents is worked out. The physical and chemical constants of the obtained compounds are defined.
Keywords: 1,2,3,4-tetrachlorobutane esterification, stearic, palmitic and oleic acid salts, erythritol esters